Sifat Keterawetan Kayu Rajumas (Duabanga moluccana Blume) Dengan Metode Perendaman Dingin: Durability Properties of Rajumas Wood (Duabanga moluccana Blume) by Cold Soaking Methods - Anggoro, Dhefa; Lestari, Andi Tri; Ningsih, Rima Vera (PERENNIAL, 2024)
Rajumas wood is a type of fast-growing wood that is included in durable class IV-V. The availability of local wood is abundant and is commonly used in West Nusa Tenggara (NTB) Province. This wood has a low durability class, so it needs special treatment, namely pickling. This research aims to determine the level of absorption, retention, and penetration of rajumas wood. The samples used were the core and sapwood of Rajumas wood. This research uses a cold soaking method with 1% biocide preservative with a soaking time of 12 hours, 24 hours, and 36 hours. The results showed that the TC sample (core part; soaking time 36 hours) produced the highest absorption and penetration values, 0.2035 g/cm3 and 0.3575 cm, respectively. Meanwhile, the GC sample produced the highest retention value (sapwood; soaking time 36 hours), namely 0.0090 g/cm3. These results show that the durability of rajumas wood in the heart and sapwood is relatively high at the absorption level, while the retention level tends to be low.